Prophylactic topical tranexamic acid versus placebo in surgical patients: a systematic review and meta-analysis - Wan Yi, Teoh; Tun Giap, Tan; Ka Ting, Ng; Ke Xin, Ong; Xue Lin, Chan; Samuel Ern Hung, Tsan; Chew Yin, Wang (Wolters Kluwer Health, Inc., 2021)
Perioperative bleeding remains a major concern to all clinicians caring for perioperative patients. Due to the theoretical risk of thromboembolic events associated with tranexamic acid (TXA) when administered intravenously, topical route of TXA has been extensively studied, but its safety and efficacy profile remain unclear in the literature. The primary aim of this review was to assess the effect of topical TXA on incidence of blood transfusion and mortality in adults undergoing surgery.